A Double Blind Study of the Effect of Tranexamic Acid in Essential Menorrhagia - Vermylen, J; Verhaegen-Declercq, M. L; Verstraete, M; Fierens, F (Thrombosis and Haemostasis, 1968)
Oral administration of tranexamic acid, in a dosage of 3 g daily from the first day of menstruation onwards, significantly decreases menstrual haemoglobin loss in women with so-called essential menorrhagia.The frequency of side-effects reported did not differ between “active” and “placebo” periods.